Alteration of miRNA expression in early endothelial cells after exposure with sub-lethal sulfur mustard concentrations. (26th February 2016) - Schmidt, Annette; Steinritz, Dirk; Thiermann, Horst; Meineke, Viktor; Abend, Michael
Highlights: miRNA levels in early endothelial cells after sulfur mustard challenge were assessed. SM had a significant impact on miRNA expression levels after low-dose SM exposure. This was accompanied with decrease of clonogenicity, increase of abnormal cells and necrosis. miRNAs are part of epigenetic control mechanisms which are linked to chronic health effects. Thus, miRNA perturbations may be involved in SM induced long-term health effects. Abstract: Background/aim: Sulfur mustard (SM) is known to induce chronic wound healing disorders as well as disturbed endothelial regeneration. It is known that wound healing as well as endothelial regeneration are controlled by micro-RNA (miRNA). As nothing is known today about the effect of SM onto miRNA expression we wanted to investigate whether there is an effect of sub-lethal concentrations of SM onto the miRNA expression of endothelial cells. Methods: Early endothelial cells (EEC) were incubated with different sub-lethal concentrations of sulfur mustard (SM) in-vitro. Cells were subsequently analyzed with respect to survival and colony-forming capacity. In addition, the nuclear structure was investigated with respect to apoptosis, micronuclei or abnormal forming using the MAA assay. Six hundred sixty-seven different miRNA species from both, treated and untreated EEC were quantified. Results: The sub-lethal concentrations IC1, IC5 or IC10 were used. While performing the MAA assay the cells showed a time dependent change in nucleus structure from normal to abnormal, without significant changes in apoptosis being observed. In the colony-forming assay a weak cell proliferation capacity was revealed. Under all conditions they lost their capacity to form colonies. Out of 667 investigated miRNAs in total 66 showed a significant change in expression upon incubation with SM. 19 miRNAs were up-regulated and 47 down-regulated. The strongest correlation between SM concentration and up-regulation was found for mmu-miR-92a-3p* (hsa-miR-92a). Seven miRNAs showed a change in expression similar to endothelial cells from younger or older mice. Conclusion: The presented work demonstrates that sulfur mustard (SM) has an effect on miRNA expression in general. The observed changes in expression in early endothelial cells correlates to the known effects of SM. Further studies have to investigate if these findings are in direct dependence and if these relationships can be used to alleviate the sulfur mustard induced clinical damage.